How can we prevent bullying experiences? The benefits of appreciating positive experiences and maintaining good social relationships - Chamizo-Nieto, María Teresa; Rey-Peña, Lourdes (My University, 2022)
Background: The phenomenon of school bullying is suffered by adolescents on different countries. Scientific literature evidences the severe negative impact on victim adolescents’ quality of life and psychological adjustment. So, numerous studies have examined risk and protective factors for victimization. Among the factors that have shown protective effects of aggressive experiences are the gratitude and the maintaining of good social relationships. Nevertheless, there is little research analysing the role of both factors in bullying contexts, even less the gratitude as possible protector factor of bullying victimization. Aims: The purpose of this study was to examine the possible protective role of gratitude on bullying victimization, and to explore the possible mediator roles of positive relationships and classmate support in the relation between gratitude and victimization in a sample of adolescents. Method: A sample of 604 students (54.14% females; Mage = 13.48; SD = 1.28) participated in the study completing some measures assessing gratitude, positive relationships, classmate support and victimization. Results: The results of mediation analyse showed the relationship between gratitude and victimization was totally mediated by positive relationships and classmate support. Conclusion: These results corroborate the importance of the development of gratitude in promoting and strengthening social relationships inside and outside classrooms. Likewise, this study provide evidence on the potential role of gratitude to prevent victimization in bullying situations. Although future research is necessary to deepen and confirm these findings.
Keywords: Acoso moral en la escuela - Congresos; Victimization; Gratitude; Positive relationships; Classmate support